Robotic liver surgery for minor hepatic resections: a comparison with laparoscopic and open standard procedures - Croner, Roland S.; Perrakis, Aristotelis; Hohenberger, Werner; Brunner, Michaela (Langenbecks Archives of Surgery, 2016)
Minimally invasive liver surgery is increasing worldwide. The benefit of the robot in this scenario is currently controversially discussed. We compared our robotic cases vs. laparoscopic and open minor hepatic resections and share the experience.From 2011 to 2015, ten patients underwent robotic and 19 patients underwent laparoscopic minor liver resections in the Department of Surgery, University Hospital Erlangen. These patients were compared to a case-matched control group of 53 patients. The perioperative prospectively collected data were analyzed retrospectively.Blood loss was significantly decreased in the robotic (306 ml) and laparoscopic (356 ml) vs. the open (903 ml) surgery group (p = 0.001). Mean tumor size was 4.1-4.8 cm in all groups (p = 0.571). Negative surgical margins were present in 94 % of the open and 100 % of the laparoscopic and robotic group (p = 0.882). Time for surgery was enlarged for robotic (321 min) vs. laparoscopic (242 min) and open (186 min) surgery (p = 0.001). Postoperative hospitalization was decreased after robotic (7 days) and laparoscopic (8 days) vs. open (10 days) surgery (p = 0.004). Total morbidity was 17 % for open, 16 % for laparoscopic, and 1 % for robotic cases (p = 0.345). Postoperative pain medication and elevation of liver enzymes were remarkably lower after minimally invasive vs. open procedures.Minimally invasive liver surgery can be performed safely for minor hepatic resections and should be considered whenever possible. Minor liver resections can be performed by standard laparoscopy equivalent to robotic procedures. Nevertheless, the robot adds a technical upgrade which may have benefits for challenging cases and major liver surgery.
EVALuna2:15231